Ethanoic Extractions of Lagerstroemia Speciosa Flowers for Dye Sensitized Solar Cell - A.O, Boyo; T, Sonaike.; R.O., Kesinro (Covenant Journal of Physical and Life Sciences, 2014)
Dye-sensitized solar cells (DSSCs) have attracted great interest as potential candidates of â€œlow cost solar cellsâ€ in the solution of global energy demand. To accelerate the progress of DSSCs, it is important to evaluate device performance with reliable measurements that will enable more effective comparison and application of new findings in materials and technologies by different research groups. In this perspective, Lagerstroemia Speciosa Flowers dye was extracted using two methods of soxhlet and cold ethanol extraction. Our findings show that the open-circuit voltage is low which might be due to reduction in electron conduction .The Conversion efficiency of cold ethanol dye extract is higher than that of the soxhlet ethanol dye extract, which indicate that the dye pigment is more degraded in the latter method. However with further investigation, the constructed DSSCâ€™s be made to serve as a power source for driving self-powered devices. Key word: - lagerstroemia speciosa flowers, Ethanol, Dye Sensitized Solar Cells